Teologiczne znaczenie osoby i natury w świetle chrystologii Soboru Chalcedońskiego - Giacomo Calore (Warszawskie Studia Teologiczne)
Council of Chalcedon is an actual closing point for Christology and a starting point for anthropology. Behind the teachings of the Council of Chalcedon, together with later clarifications added by the Second and the Third Councils of Constantinople, there were centuries of dispute between the School of Alexandria and the School of Antioch about the person and natures of Christ (4th/5th – 7th centuries). Therefore the light shed on the man by patristic Christology concerns understanding of his being a person and his nature. The analysis of the Council’s teachings of faith shows that these two concepts belong to two different areas which means that every man, following the man Jesus, is a person whose dignity is on a different level than his natural features (mind, will, consciousness, etc.) – in other words, it originates from transcendence. Simultaneously, person is a relational reality because it puts a man in a relation with God in which the nature can be improved, the nature whose essence – since it was adopted by Logos – is to be capax Dei, or ability to grow in following Christ.